Goldstein, Jorge. Patenting Life: Tales from the Front Lines of Intellectual Property and the New Biology - Lerner, Josh (Journal of Economic Literature, 2026)
Josh Lerner of Harvard University and NBER reviews “Patenting Life: Tales from the Front Lines of Intellectual Property and the New Biology” by Jorge Goldstein. The Econlit abstract of this book begins: “Explores the legal, commercial, and social debates surrounding the patenting of biological materials, whether living single cells, whole plants or animals, or the inert molecules that they produce or from which they are made.”